1988
DOI: 10.1128/aac.32.4.561
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic advantages of erythromycin estolate over ethylsuccinate as determined by high-pressure liquid chromatography

Abstract: The pharmacokinetics of erythromycin estolate (500 mg) and erythromycin ethylsuccinate (600 mg) were compared in 12 healthy volunteers after single doses and after repeated oral doses (every 8 h). High-pressure liquid chromatography with electrochemical detection was used to determine concentrations in plasma and urine of estolate, ethylsuccinate, and erythromycin base. The maximum concentration of drug in the serum, the half-life, and the area under the curve for erythromycin estolate were significantly great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
2
20
0
1
Order By: Relevance
“…Human oral erythromycin studies have demonstrated that single dose plasma levels poorly predict those obtained following multiple doses, with observed AUC and Cmax exceeding those predicted from single dose data (Welling et al, 1979;Croteau et al,, 1988;Colburn et al, 1977). Likewise, in the present study, we demonstrated similar differences between single and multiple doses of erythromycin phosphate.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Human oral erythromycin studies have demonstrated that single dose plasma levels poorly predict those obtained following multiple doses, with observed AUC and Cmax exceeding those predicted from single dose data (Welling et al, 1979;Croteau et al,, 1988;Colburn et al, 1977). Likewise, in the present study, we demonstrated similar differences between single and multiple doses of erythromycin phosphate.…”
Section: Resultssupporting
confidence: 73%
“…The greater total serum antibiotic content achieved with erythromycin estolate has been attributed in part to better bioavailability (Welling et al, 1978). In addition, studies in humans demonstrate greater total serum antibiotic content achieved with erythromycin estolate than with erythromycin ethylsuccinate (Croteau et al, 1988;Bechtol, 1976). In contrast, statistical differences between pharmacokinetic parameters for erythromycin estolate and erythromycin ethylsuccinate were not demonstrated in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Examination of the second peak revealed that it occurred close to volunteers' midday meals, suggesting biliary recycling may be the cause. This phenomenon in human was also reported by Croteau [21]. Pharmacokinetic parameters, listed in Table 4, were calculated by statistical moment analysis using DAS software (Version 1.0, Medical Institute of Wannan, China).…”
Section: Clinical Applicationmentioning
confidence: 96%
“…A few studies have used a fluorometric assay (DiSanto et al 1980;Tserng & Wagner 1976) for separation of erythromycin and erythromycin propionate. More recently, specific high performance liquid chromatography (HPLC) assays have been utilised (Birkett et al 1990;Croteau et al 1988;Stubbs & Kanfer 1989). In addition, most of the pharmacokinetic data has been derived using oral erythromycin products.…”
Section: Erythromycinmentioning
confidence: 99%